Case Report: Can early full-course tocilizumab therapy reverse vascular stenosis in Takayasu arteritis? - Hu, Congqi; Liu, Lingjie; Xiao, Hui; Zhao, Hongjun; Chen, Guangxing; Xie, Yanli (Frontiers in Immunology, 2025)
Takayasu arteritis (TAK) is an idiopathic systemic disease characterized by granulomatous inflammation of the aorta and its branches. TAK can cause multiple vascular injuries throughout the body, mainly arterial stenosis and aneurysms. In severe cases, it can even lead to fatal hemorrhage, infarction and other serious complications, posing a serious threat to the patient’s life and health. Few studies have shown that drug treatment can improve or reverse its vascular stenosis. This study describes a 19-year-old woman diagnosed with TAK who had multiple vascular stenosis at the time of the disease. In an early and timely manner as well as up to seven years after a full course of tolizumab, her vascular wall thickening improved and previously stenotic vessels were recanalized. We believe that early use of tocilizumab in patients with TAK can improve vascular lesions. To our knowledge, this study is the first case to find complete recanalization of stenotic vessels after the use of tocilizumab, and the pre- and post-test and examination data are complete. In addition, we summarized the cases of improvement of vascular lesions after tocilizumab treatment of TAK, and preliminarily compared the efficacy and safety of tocilizumab and TNFi in TAK. We speculate that early and adequate use of tocilizumab could reverse early inflammatory vessel wall thickening and stenosis, and we found, through further literature review, that its efficacy was comparable to that of TNF inhibitors